2022
DOI: 10.3390/ma16010339
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and RSM-Based Process-Parameters Optimisation for Turning Operation of EN36B Steel

Abstract: The main objective of this article is to perform the turning operation on an EN36B steel work-billet with a tungsten carbide tool, to study the optimal cutting parameters and carry out an analysis of flank-wear. Experimental and simulation-based research methodology was opted in this study. Experimental results were obtained from the lab setup, and optimisation of parameters was performed using RSM (response surface methodology). Using RSM, cutting-tool flank-wear was optimised, and the cutting parameters whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, with an increase in the depth of cut from 0.2 mm to 0.3 mm, the value of V b increases sharply in a linear fashion with a higher cutting speed range. Kumar et al (2023) and Parida and Maity (2019) also witnessed similar variations in the values of V b with changes in input turning parameters during the machining of EN36B steel and Monel-400 alloy, respectively. The steep curvature in factor A, as observed in the perturbation plot [Figure 11(a)], indicates that the response (V b ) is more sensitive to cutting speed (A) as compared to feed rate (B) and depth of cut (C).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…However, with an increase in the depth of cut from 0.2 mm to 0.3 mm, the value of V b increases sharply in a linear fashion with a higher cutting speed range. Kumar et al (2023) and Parida and Maity (2019) also witnessed similar variations in the values of V b with changes in input turning parameters during the machining of EN36B steel and Monel-400 alloy, respectively. The steep curvature in factor A, as observed in the perturbation plot [Figure 11(a)], indicates that the response (V b ) is more sensitive to cutting speed (A) as compared to feed rate (B) and depth of cut (C).…”
Section: Resultsmentioning
confidence: 63%
“…Similarly, Lakshmikanthan et al (2023) also used RSM and observed cutting speed as the most crucial factor for surface roughness during the turning of aluminum alloy (LM13) metal matrix composite. Other studies performed by Surya (2022) and Kumar et al (2023) also used the RSM technique to obtain optimal settings of input machining parameters while turning Ti6Al4V titanium alloy and EN36B steel, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also used ANNOVA and other optimization techniques [10][11][12][13][14] for the study of vibration characteristics, fracture analysis [15][16] and in biomedical applications [17][18][19]. Latest computational tools FEA, RSM and Taguchi are useful in design and optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon same study, in present research work design of experiments and ANNOVA has been used. In continuation [34][35][36] they have studied the mechanical systems using modern tools like modal analysis, loose transmission gearbox bolt condition analysis, bone fracture analysis [37][38][39]. In this research work simulation and experimental work was performed and there results were compared for final conclusions.…”
Section: Introductionmentioning
confidence: 99%